Goûts et préférences actuels des téléspectateurs inuits en Terre de Baffin, au Keewatin dans les Territoires du Nord-Ouest - Valaskakis, Gail; Wilson, Thomas (Anthropologica, 2022)
This paper describes an audience survey conducted early in 1984 of television viewing tastes and habits among the Inuit of the Eastern and Central Arctic. The authors examine television viewing habits in relation to specific characteristics of the Inuit population such as age, sex, language, and education. It was found that news and public affairs programing in both English and Inuktitut were the most popular, and that there was also considerable interest in situation comedies and soap operas. The results of this survey are discussed in the context of efforts by the Inuit Broadcasting Corporation to provide Inuktitut-language television for the Canadian North